Pencegahan kanker serviks dengan Penyuluhan dan Pemeriksaan Pap Smear di Kedaton, Pleret, Bantul: Indonesia - Wijayanti, Arini Rizky; Luki Tiara, Dinda; Widayati, Sri; Kharisma, Muhammad (UII, 2024)
Cervical cancer is the second most common type of cancer in Indonesia. One of the factors affecting the high incidence of cervical cancer in Indonesia is the low coverage of screening and early detection, such as Pap smear. The low coverage is caused by various factors, including health system and lack of public awareness. Therefore, this community service focus on cervical cancer counseling and Pap smear examination. The purpose of this activity are to increase public awareness of cervical cancer and the coverage of cervical cancer screening in community. The activity was carried out in Kedaton, Pleret, Bantul with 26 participants. As many as 57.69% of the participants were first-time Pap smear takers. Pap smear diagnostic results showed that all participant did not have cervical epithelial abnormalities leading to malignant lesion (Negative for Intraepithelial Malignancy) but there were participant with epithelial reactive changes due to inflammation (23.08%), actinomycosis (15,38%), bacterial vaginosis (11.54%) and IUD-related reactive changes (3.8%). The majority of patients with reactive changes and infection of the cervix had no complaints, indicating a lack of understanding the sign of abnormal vaginal discharge. This community service is effective to prevent cervical cancer and increase knowledge about gynecological and reproductive health. However it still requires the cooperation of many parties to expand Pap smear coverage and implementation of periodic examination.